2013
DOI: 10.1080/10408398.2012.710279
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review about Human Exposure to Polychlorinated Dibenzo-p-Dioxins (PCDDs), Polychlorinated Dibenzofurans (PCDFs) and Polychlorinated Biphenyls (PCBs) through Foods

Abstract: Dioxins include polychlorinated dibenzo-p-dioxins (PCDDs), polychlorinated dibenzofurans (PCDFs), and part of polychlorinated biphenyls (PCBs). Only the compounds that are chlorinated at the 2,3,7, and 8 positions have characteristic dioxin toxicity. PCDDs, PCDFs and PCBs accumulate in the food chain due to their high lipophilicity, high stability, and low vapor pressure. They are not metabolized easily; however their hydroxylated metabolites are detected in feces. They cause a wide range of endocrine disrupti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(33 citation statements)
references
References 157 publications
(84 reference statements)
0
32
0
Order By: Relevance
“…Polychlorinated biphenyls (PCBs) are organochlorine compounds that were once widely manufactured worldwide for industrial use (Fernandez-Gonzalez et al 2015). Although their production in the United States was banned in the 1970s and their use today is highly controlled, PCBs persist in the environment and accumulate in the food web (Bell 2014; Fernandez-Gonzalez et al 2015).…”
Section: Polychlorinated Biphenylsmentioning
confidence: 99%
“…Polychlorinated biphenyls (PCBs) are organochlorine compounds that were once widely manufactured worldwide for industrial use (Fernandez-Gonzalez et al 2015). Although their production in the United States was banned in the 1970s and their use today is highly controlled, PCBs persist in the environment and accumulate in the food web (Bell 2014; Fernandez-Gonzalez et al 2015).…”
Section: Polychlorinated Biphenylsmentioning
confidence: 99%
“…As one group of POPs, polychlorinated dibenzo-p-dioxins and polychlorinated dibenzofurans (PCDD/Fs) were widespread in environment (Barghi et al, 2016;Fernandez-Gonzalez et al, 2015;Li et al, 2016a;2016b;Schuhmacher et al, 2013Schuhmacher et al, , 2014Squadrone et al, 2016). Stockholm Convention indicated that medical waste incinerator (MWI) was a key source of PCDD/Fs emission.…”
Section: Introductionmentioning
confidence: 99%
“…Dioxins are a group of highly persistent chemical by-products of industrial process and by-products of combustion of organic material. Due to high lipophilicity and resistance to biological and environmental degradation, dioxins are able to bioaccumulate and biomagnify in food chains, which increases the potential burden of exposures to apex animals such as humans [9]. Despite significant decreases in the production of dioxin and DLCs, high persistence and bioaccumulation of these compounds results in omnipresence of dioxins [10].…”
Section: Introductionmentioning
confidence: 99%